2016
DOI: 10.1186/s13613-016-0160-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of soluble CD14 subtype (Presepsin) for sepsis and community-acquired pneumonia in ICU patients

Abstract: Background:The soluble CD14 subtype, Presepsin, appears to be an accurate sepsis diagnostic marker, but data from intensive care units (ICUs) are scarce. This study was conducted to evaluate the diagnostic and prognostic value of Presepsin in ICU patients with severe sepsis (SS), septic shock (SSh) and severe community-acquired pneumonia (sCAP). Methods:Presepsin and procalcitonin (PCT) levels were determined for patients at admission to ICU. Four groups have been differentiated: (1) absence or (2) presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
92
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 43 publications
11
92
4
2
Order By: Relevance
“…However, comparison of our results with those obtained in these studies is not possible due to differences in the criteria for classification of patients. In other setting, Klouche et al [42] have reported a ROC AUC value of 0Á80 for PCT to differentiate infected from noninfected patients in ICU patients, which is also lower than in our study (ROC AUC: 0Á904). Recently, PCT was reported as an accurate diagnostic marker, with a ROC AUC value of 0Á84, for pneumonia in patients presenting to ED with dyspnoea [41].…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…However, comparison of our results with those obtained in these studies is not possible due to differences in the criteria for classification of patients. In other setting, Klouche et al [42] have reported a ROC AUC value of 0Á80 for PCT to differentiate infected from noninfected patients in ICU patients, which is also lower than in our study (ROC AUC: 0Á904). Recently, PCT was reported as an accurate diagnostic marker, with a ROC AUC value of 0Á84, for pneumonia in patients presenting to ED with dyspnoea [41].…”
Section: Discussioncontrasting
confidence: 89%
“…Recently, PCT was reported as an accurate diagnostic marker, with a ROC AUC value of 0Á84, for pneumonia in patients presenting to ED with dyspnoea [41]. In other setting, Klouche et al [42] have reported a ROC AUC value of 0Á80 for PCT to differentiate infected from noninfected patients in ICU patients, which is also lower than in our study (ROC AUC: 0Á904). A similar performance (ROC AUC: 0Á780) has been reported by Koch et al [43] to discriminate between sepsis and nonsepsis in critically ill patients.…”
Section: Discussioncontrasting
confidence: 78%
“…The data obtained seem to demonstrate the role of this biomarker in providing prognostic information also in COVID-19 patients, as already described in several different diseases [3][4][5][6][7], allowing to identify, during the early phase of the monitoring, the patients suffering from a more severe disease which will be hospitalized for a more long time. The elevation of PSP, resulting from a dose-response mechanism of the host-pathogen interaction, occurs in the initial phase of the pathogen recognition, and remains elevated during several days on the basis of the disease severity [13] underlining the additional value of the biomarker in the prognostic assessment of patients [5][6][7]13]. Our study presents some limitations, namely the unavailability of the sample at admission to measure PSP and the limited number of died patients which does not allow a reliable evaluation of the value of PSP in mortality prediction.…”
Section: To the Editorsupporting
confidence: 69%
“…Soluble cluster of differentiation (CD) 14 subtype (sCD14-ST; 64 amino acids, 13 kDa), also termed presepsin (PSP), a small soluble peptide generated from soluble CD14, is known to function as a regulatory factor that can modulates immune responses by interacting with T and B cells [3]. Currently, the results of many clinical studies indicated that PSP is a useful biomarker not only for early diagnosis, but also for risk stratification, and prognosis prediction in sepsis patients as well in patients suffering from pneumonia [4][5][6][7]. In order to verify the potential usefulness of this biomarker in risk stratification of patients (n = 75) suffering from COVID-19 microbiology proven infection (Table 1), PSP measurement in lithium-heparin plasma samples using a chemiluminescent enzyme immunoassay (CLEIA) (Pathfast, Chemical Medience Corporation, Tokyo, Japan), was carried out in addition to routine laboratory tests performed during the period of hospitalization (from January to March 2020) in the intensive care unit (ICU, n = 21, 28%) and/or in infectious disease ward (IW, n = 54, 72%).…”
Section: To the Editormentioning
confidence: 99%
“…Most studies in the adult critical care setting have focused on comparing presepsin with PCT. Generally, the performance of presepsin has been described as comparable to that of PCT, with no real advantage gained from using presepsin as a separate, stand-alone biomarker [71,86,87]. This has also been demonstrated in various medical wards outside of the critical care environment [72].…”
Section: Adults Icumentioning
confidence: 99%